A phenomenological research on the role of emotional orientation in academics’ professional lives - DİDİN ALA, ŞEYMA NUR; BAKİOĞLU, AYŞEN (My University, 2022)
The aim of this study is to explore the role of emotional orientations in academics‟ professional life. This qualitative study was designed in accordance with the phenomenological design. In the study, the researchers used criterion-based sampling and involved 26 volunteer academics with different titles and higher institutions. The data in this study were collected through face to face in-depth interviews with semi-structured interview questions. The collected data were analyzed through content analysis in three cycles. The results of the study showed that the unique professional characteristics of academics were determinative in emotional orientations that were positive outputs such as trust, helpfulness, and tendency to work collectively. As triggering factors of emotional orientations, it was found that working alone or job-centering efforts play important roles in academics‟ practices. Another result of the research indicated that academics also produce unique emotional experiences in the context of higher education. In other words, this study reveals that emotional orientations have an effect on both positive and negatives roles in shaping academic‟ life.
Keywords: Academics‟ emotions; Emotional orientation; Observation; Life praxis; Reality; Altruism